Improving Employee Performance Through Work-Life Balance: a Study on the Mediation of Job Satisfaction and Work Stress at Pln Aceh Province - Pane, Sri Gustina (Universitas Mercu Buana, 2025)
Objectives: This study examines the relationships between Work-Life Balance (WLB), job satisfaction, work stress, and employee performance. The aim is to explore how WLB directly influences job satisfaction and employee performance, while also assessing the mediating role of job satisfaction and the moderating effect of work stress.Methodology: A quantitative approach was used, employing a survey method. Data were collected from 160 employees of PLN in Aceh Province through simple random sampling, resulting in 135 valid responses. Structural Equation Modeling (SEM) was applied using SmartPLS to analyze the correlations between the variables.Findings: The study reveals that WLB significantly enhances both employee performance (0.648) and job satisfaction (0.794). Moreover, WLB is negatively correlated with work-related stress (-0.221). Job satisfaction mediates the relationship between WLB and employee performance (0.11), while WLB indirectly boosts performance by reducing work stress (0.68).Conclusion: Work-life adjust features a considerable positive affect on representative execution by cultivating work fulfillment and diminishing work-related push. Empowering WLB through adaptable approaches and wellness activities can upgrade worker well-being and contribute to made strides organizational execution.